2013
DOI: 10.1186/1746-1596-8-201
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localization of protein arginine methyltransferase-5 correlates with grade of lung tumors

Abstract: BackgroundProtein arginine methyltransferase-5 (PRMT5) is a chromatin-modifying enzyme capable of methylating histone and non-histone proteins, and is involved in a wide range of cellular processes that range from transcriptional regulation to organelle biosynthesis. As such, its overexpression has been linked to tumor suppressor gene silencing, enhanced tumor cell growth and survival.Material and methodsQuantitative real-time polymerase chain reaction, Western immunoblot and immunohistochemistry were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 29 publications
4
39
0
Order By: Relevance
“…Among PRMTs, PRMT5 appears to play a particularly relevant role in the regulation of cell death and malignant transformation processes in mouse and humans (3538). Indeed, PRMT5 is up-regulated in various human lymphoid malignancies (3941) and solid tumors (42–48) and promotes cancer cell proliferation and survival (38, 46, 49, 50). This has led to the development of selective PRMT5-inhibiting drugs such as CMP5 and EPZ015666 as a potential new therapy in cancer (43, 51, 52).…”
Section: Introductionmentioning
confidence: 99%
“…Among PRMTs, PRMT5 appears to play a particularly relevant role in the regulation of cell death and malignant transformation processes in mouse and humans (3538). Indeed, PRMT5 is up-regulated in various human lymphoid malignancies (3941) and solid tumors (42–48) and promotes cancer cell proliferation and survival (38, 46, 49, 50). This has led to the development of selective PRMT5-inhibiting drugs such as CMP5 and EPZ015666 as a potential new therapy in cancer (43, 51, 52).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of PRMT5 has been studied in various types of cancers, and its localization, nuclear and/or cytoplasmic, appears to vary depending on the organs of origin and/or histological types . The diverse biological functions of PRMT5 may be explained by distinct intracellular localization and its binding partners.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many previous studies showed the expression and functions of proteins and genes in lung cancer, and it may be significantly related to tumor progression and metastasis [23-26]. …”
Section: Discussionmentioning
confidence: 99%